Systemic Immunosuppression by Methylprednisolone and Pregnancy Rates in Goats Undergoing the Transfer of Cloned Embryos. Issue 4 (18th June 2014) - Feltrin, C; Cooper, CA; Mohamad‐Fauzi, N; Rodrigues, VHV; Aguiar, LH; Gaudencio‐Neto, S; Martins, LT; Calderón, CEM; Morais, AS; Carneiro, IS; Almeida, TM; Silva, ING; et al.
Contents The presence of the zona pellucida has been perceived as a requirement for the oviductal transfer of cloned embryos at early stages of development while protecting the embryo from an immune system response. We hypothesized that steroid hormone therapy could reduce a potential cellular immune response after the transfer of zona‐free cloned embryos into the oviduct of recipient female goats. In Experiment 1, seven does were used to study the systemic immunosuppressant effect of the methylprednisolone administration (for 3 days) on blood cell counts. Whole blood was collected prior to treatment with methyprednisolone and then on Days 1, 2, 3, 4, 7, 14, 21 and 28 after the first dose of methylprednisolone for the analysis of haematological parameters. Methylprednisolone treatment significantly reduced circulating white blood cells and neutrophils in comparison with pre‐treatment levels, demonstrating a systemic immunosuppressant effect. In Experiment 2, a group of 58 does were used as recipient females to study the effect of administration of methylprednisolone for 3 days on the establishment of pregnancies after the transfer of zona‐free cloned embryos into the oviducts. No effects on pregnancy rates on Day 30 were observed regarding the distinct treatment groups (control vs. methylprednisolone), the source of oocytes (in vivo‐ vs in vitro‐matured) or the presence or absence of the zona pellucida in embryos. In summary, methylprednisolone was effective at inducing a systemic immunosuppressed state in goats, but the treatment prior to embryo transfer did not affect pregnancy rates. Moreover, pregnancy rates were similar between zona‐free and zona‐intact goat cloned embryos.